Total Productive Maintenance Analysis of Wrapping Machine Line 4 through Overall Equipment Effectiveness and Six Big Losses at PT XY, Cirebon – West Java - Ayu Anggraeni Sibarani; Katon Muhammad; April Yanti (Jurnal Rekayasa Sistem & Industri, 2020)
PT. XY is a company engaged in the food industry, namely instant noodles. The problem encountered atPT XY was that one of the machines that used in instant noodle production often stopped operating due toa breakdown. The machine that often experiences breakdowns is the Wrapping Line 4 machine, which is apackaging machine for cup noodle products. This results in a long machine downtime so that theproduction target is not achieved. One approach to addressing this problem is Total ProductiveMaintenance (TPM) which is measured through Overall Equipment Effectiveness (OEE) and Six BigLosses. This study aims to calculate the Overall Equipment Effectiveness (OEE) value, calculate the valueof the Six Big Losses factor and determine the root cause of the dominant problem of the Six Big Lossesfactor using a fishbone diagram. The calculation results show that the OEE value on the Wrapping Line 4is below the international standard, which is 78.03%. Dominant factors that cause machine effectivenesswas low are quality defect losses by 63,54% and reduce speed losses by 24,87%.